Urinary glyphosate, selenium status, and their impact on mortality: Evidence from NHANES 2013–2018 - Pei-Lun Chu; Ching-Chung Hsiao; Ta-Chen Su; Chikang Wang; Chien-Yu Lin (Ecotoxicology and Environmental Safety)
Purpose: Glyphosate and glyphosate-based herbicides (GBHs), extensively used worldwide, have been associated with various health concerns, including an elevated risk of mortality. Experimental studies suggest that these herbicides may disrupt selenium homeostasis by hindering its uptake or promoting oxidative stress. However, the interplay between glyphosate exposure and selenium status remains poorly understood in epidemiological studies, particularly regarding selenium's role in modulating the mortality risk associated with glyphosate exposure in nationally representative populations. Approach and results: In this study, we analyzed data from the 2013–2018 National Health and Nutrition Examination Survey (NHANES), which included 6410 participants aged 3 years and older. This dataset was linked to mortality information from the National Center for Health Statistics (NCHS) for individuals aged 18 and older, with follow-up through 2019. The primary aim was to investigate the relationships between urinary glyphosate levels, whole blood selenium, selenium intake, and the influence of selenium status on glyphosate-related all-cause mortality risk. A significant negative correlation was observed between the natural logarithm (ln) of urinary glyphosate levels and the ln of whole blood selenium in the complex multiple linear regression models, with a ß coefficient of −0.010 (SE = 0.003, P = 0.003). However, no association was found between urinary glyphosate levels and selenium intake. Furthermore, the association was particularly prominent among females, non-Hispanic whites, and individuals with lower selenium intake. When examining the relationship between glyphosate exposure, whole blood selenium levels, and all-cause mortality, higher ln-urinary glyphosate levels were significantly associated with an increased risk of mortality (Hazard Ratio [HR] = 1.43; 95 % CI: 1.00–2.09). This elevated risk was especially pronounced in individuals with whole blood selenium concentrations at or above the 50th percentile. Additionally, ln-whole blood selenium was associated with a protective effect against all-cause mortality (HR = 0.01; 95 % CI: 0.00–0.18), with the strongest protective effect observed in individuals with selenium levels below the 50th percentile. Conclusions: In this comprehensive analysis of NHANES data, our study identifies a potentially harmful relationship between glyphosate exposure and whole blood selenium levels. Notably, excessively high whole blood selenium levels may not only reduce the protective effects against all-cause mortality but could also increase the risk of glyphosate-related mortality, suggesting a U-shaped relationship between selenium levels and mortality risk. These findings highlight the need for further research into the health effects of glyphosate exposure and its interaction with selenium status, emphasizing the potential public health implications.